Using otolith and body shape to discriminate between stocks of European anchovy (Engraulidae: Engraulis encrasicolus) from the Aegean, Marmara and Black Seas - Durrani, Omerhan; Bal, Habib; Battal, Zeynep Selva; Seyhan, Kadir (Wiley, 2022)
European anchovy, a small pelagic fish, plays a significant role in the blue economy, with remarkable commercial, ecological and culinary values. In this study, the variability in the shapes of the body and sagitta otoliths was examined to identify the different anchovy stocks in the Black Sea (26.5 degrees E-39.9 degrees E, 38.7 degrees N-42.1 degrees N) and adjacent regions, i.e., the Sea of Marmara and the Aegean Sea. The body shape was assessed with geometric morphometrics, while shape indices and elliptic Fourier analysis were used to evaluate the shape of the sagitta otoliths. The data were analysed using multivariate and univariate analysis of variance, discriminant function and principal component analysis. The anchovy population could be divided into five distinct stocks based on body shape, with an overall leave-one-out cross-validated correct classification of 85.6%. The geometric morphometrics revealed significant differences in body depth, snout, lower jaw and caudal fin. The differences in sagitta otolith shape also revealed the existence of four distinct stocks with an overall leave-one-out cross-validated correct classification of 46.5%-69.3%. The elliptic Fourier analysis revealed two main stocks of anchovy from the Black Sea as the Eastern-Middle Black Sea stock and the Western Black Sea stock. Based on the elliptic Fourier analysis, the differences in the sagitta otoliths increase in magnitude with increasing geographic separation, first manifested at the otolith anterior notch, followed by changes in the otolith width. The findings affirmed the existence of distinct stocks that should have important implications for effective management of this pelagic fish in the Black Sea and adjacent regions.
Keywords: elliptic Fourier analyses; geometric morphometrics; population structure; stock discrimination; Turkiye